EXPLORING LEARNING ENGAGEMENT AND SELF- EFFICACY IN SHAPING TRAINEES’ EXPERIENCES AT LPK ANANDA PERKASA MULIA - Solehudin (JURNAL ASIK, 2025)
This study explores the role of learning engagement and self-efficacy in shaping trainees’ experiences at LPK Ananda Perkasa Mulia, a vocational training institution. It aims to understand how different levels of engagement and confidence influence trainees’ participation, persistence, and skill mastery. Employing a qualitative descriptive research design, data were collected through interviews, observations, and document analysis of trainees across various training programs. The findings reveal that behavioral, emotional, and cognitive engagement vary among trainees, influenced by curriculum relevance, peer interaction, and instructor facilitation. Self-efficacy levels also differ, with mastery experiences, verbal encouragement, and peer modeling serving as key drivers. A reciprocal relationship between engagement and self-efficacy was identified, where each enhances the other to promote deeper learning and satisfaction. Barriers such as limited prior knowledge and lack of personalized support were also found to affect these dynamics. The study suggests that mastery-based learning, peer mentoring, and tailored interventions are essential for optimizing training outcomes. These insights provide valuable implications for improving vocational training programs to better prepare trainees for workplace demands.